THE EFFECT OF PROBLEM-BASED LEARNING MODEL WITH TARL APPROACH ON NATURAL AND SOCIAL SCIENCES LEARNING OUTCOMES AND CRITICAL THINKING SKILLS IN ELEMENTARY SCHOOL - Slamet Tri Widodo; Ana Fitrotun Nisa; Heri Maria Zulfiati (Universitas Majalengka, 2025)
This research investigates the effect of integrating the Problem-Based Learning (PBL) model with the Teaching at the Right Level (TaRL) approach on fifth-grade students’ critical thinking skills and learning outcomes in natural and social sciences. The background highlights low student achievement and inadequate critical thinking, often caused by conventional, teacher-centered methods that fail to accommodate individual differences. Using a quasi-experimental design with a nonequivalent control group (N=56), students were divided into experimental and control classes. The experimental class received PBL-TaRL instruction over eight weeks (16 sessions), while the control class followed conventional teaching. Pretests and posttests were used to assess both critical thinking and learning outcomes. MANOVA results (Wilks’ Lambda = 0.029; p < 0.05) revealed significant differences, with the experimental class showing greater improvement and very large effect sizes (partial eta squared: 0.970 and 0.958). These findings demonstrate that combining PBL and TaRL fosters higher-order thinking and academic achievement by promoting active engagement and adapting materials to students’ proficiency levels. This research recommends broader implementation of PBL-TaRL within the Merdeka Curriculum and highlights the need for teacher training in task design and differentiation to maximize its impact in primary schools.